The chromatic cadences of Nicola Vicentino - Nogueira, Marcos Pupo [UNESP]; Peinado Pereira, Maria Clara [UNESP] (Assoc Nac Pesquisa & Pos-graduacao & Musica, 2021)
Nicola Vicentino (1511-1576/1577) was an important Italian musician and theorist who widely discussed chromatic music in the 16th century. His treatise, L 'antica musica ridotta alla moderna prattica (1555), on the application of Greek genera practiced at the time is an important source for understanding the chromatic music of this period. Chromaticism of 16th-century music is still comprehended in many divergent ways by researchers in this area. Seeking greater depth in this aspect of the repertoire, the present study aims to elucidate the cadential foundations of Vicentino's chromatic music presented in his treatise and examine the composer's use of this theory in his compositional practice. To achieve this aim, we conducted a bibliographic review of the main works about Vicentino and his theory in parallel with a careful examination of his treatise, the main source of his ideas, and some other contemporary writings of the author. The focus was placed on the particular aspects of the theory of chromaticism proposed by Vicentino, the premises of his compositional thinking, and its possible practical applications. As a result, we present the structure and peculiarities of Vicentino's cadential movements, tracing the relationship of these peculiarities to his theory and demonstrating the composer's use of chromatic cadences in pieces of his treatise and his fifth book of madrigals (1572).
Keywords: Nicola Vicentino; Sixteenth-century music; Chromaticism; Cadences